Gel properties of myofibrillar protein as affected by gelatinization and retrogradation behaviors of modified starches with different crosslinking and acetylation degrees. (November 2019) - Fan, Mingcong; Huang, Qilin; Zhong, Saiyi; Li, Xuxu; Xiong, Shanbai; Xie, Jing; Yin, Tao; Zhang, Binjia; Zhao, Siming
Abstract: The gelatinization and retrogradation behaviors of crosslinked/acetylated tapioca starches (CA-TS) as affected by crosslinking and acetylation degrees were studied. Likewise, the influence of gelatinization and retrogradation of CA-TS on the gel properties of fish myofibrillar protein (MP) was investigated at the weight concentrations of 6.0% MP and 0.3% CA-TS. Highly-crosslinked TS had a higher pasting temperature and heat-stability, and lower gelling capacity than other CA-TS, while highly-acetylated TS had a lower pasting temperature and higher peak viscosity. X-ray diffraction (XRD) results showed the characteristic diffraction peaks of native CA-TS disappeared after gelatinization and did not reappear after retrogradation. However, polarized light micrographs showed bright spots in the retrograded MP/CA-TS gels. Additionally, high level of crosslinking delayed the water-absorption, swelling and rupture of starch granules, further inhibiting their concentrating and filling effects within the MP network. But high level of acetylation enabled the starch gelatinization to occur before the complete gelation of MP, thus interfering with the formation of MP gel network. Meanwhile, low-crosslinked/acetylated TS exhibited a suitable pasting temperature (>61 °C), relatively high peak viscosity and gelling capacity, which can significantly enhance the storage modulus G′ and textural properties of MP. Furthermore, the rapid increase in the G′ of MP/CA-TS composites during cooling (90 → 20 °C) indicated that the partial crystal CA-TS might act as a semi-rigid filler that enhanced the MP gel strength. SEM photographs showed the formation of an extremely homogeneous and compact MP network in presence of low-acetylated TS in contrast to a loose network in presence of highly-acetylated TS. Graphical abstract: Image 1090 Highlights: Crosslinking of modified starch raised pasting temp and inhibited swelling and gelling. Suitable CA-TS pasting temp, swelling and gelling are beneficial to MP gel. Low level of crosslinking/acetylation of starch enhanced MP gel strength. High crosslinking and acetylation hindered starch concentration/filling effects and MP gelation. Retrograded starches exist as a semi-rigid filler that enhanced MP gel strength.